Mycotoxins as emerging risks: from dietary exposure to urinary biomarkers - Martins, Carla (2018)
Daily life human exposure to several chemical contaminants is a known reality and ingestion of food products constitutes one of the main routes of this exposure. Mycotoxins, secondary metabolites of fungi, contaminate food and assume particular importance in Public Health, regarding their potential toxic effects. Considering that mycotoxins occurrence in foods has been frequently reported, in diversified foodstuffs, at low concentrations, it is expected a chronic exposure to mycotoxins in the Portuguese population. Biomonitoring is a relevant key tool to accurately characterize this exposure. In addition, as health-based guidance values are established only for food intake, it is of the utmost importance to find a correlation between urinary biomarkers and food intake. Previous studies had reported associations between food intake and mycotoxins related urinary biomarkers, particularly for DON, OTA and FB1. It is intended, for the first time in Portugal, to estimate the exposure of the population to multiple mycotoxins through the determination of urinary biomarkers and to develop a model of association between biomarkers concentrations and food consumption. An epidemiological, observational and cross-sectional study will be developed, with the analysis of 24-hour urine samples at individual level, in a sub-sample of participants in the recent National Food and Physical Activity Survey. Expected results will contribute: i) to estimate the Portuguese population exposure to mycotoxins, allowing to identify groups of the population more exposed and consequently more vulnerable, and ii) to design intervention strategies at the health promotion level leading to the empowerment of the population to select an adequate diet. Furthermore, and considering the potential consequences of climate change on mycotoxins occurrence in food, this study will allow to anticipate the potential risk associated to mycotoxins exposure in a climate change scenario.